Production Of Spatial Geosite Itinerary Maps as Tourism Destinations - Jasman Jasman; Masri Ridwan; Moh Khairul Amri Kamarudin; Darwin Parlaungan Lubis (JURNAL GEOGRAFI, 2023)
The availability of tourist maps so far has experienced limitations in presenting attribute data in the form of non-spatial characteristics. Tourism is called quality if it can convey the information the community needs. Among them are location attributes, land use, natural and cultural phenomena history, and interrelationships between spaces. Geographical and cultural features are essential to be used in realizing quality tourism through the availability of information on tourism space areas, such as visualization of landscapes and depth of local cultural knowledge. This study used a qualitative method with data collection techniques carried out through interviews, focus group discussions, landscape documentation, surveys, and observations to determine the geographical position of spatial elements. The results of the study produced Itinerary Maps and geosite distribution, including the Saddang River, Buntu Lindo Batu, Lo'ko Malillin, Buntu Lingkobo, Mount Benteng Alla’, Buntu Karua, and Kalosi Arabica Coffee Cultivation. The row of geosites has a chronology and chronology of formation and is related to the social culture of the people in the Fort Alla’ area. The findings from this study are expected to provide exposure to the public, tourists, and the government to preserve natural and cultural heritage to become a reference in implementing sustainable tourism development in Enrekang Regency. It is necessary to develop a digital-based information system that presents spatial attribute data and ethnographic records that can be accessed online. Keyword: Tourism Geography, Ethnography, Benteng Alla’, GIS